1994
DOI: 10.1111/j.1651-2227.1994.tb13075.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and skeletal maturation in children with phenylketonuria

Abstract: Growth and skeletal maturation was evaluated in 82 children participating in the German Collaborative Study of Children Treated for Phenylketonuria (PKU). Height, weight, head circumference and bone age were recorded at regular intervals for the first 6 years of life. The mean SD score (SDS) for height was not significantly different from zero at study entry, but decreased mainly during the second year of life to a nadir of -0.78 in boys and -0.54 in girls at 2.5 years. During the subsequent years, a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 26 publications
3
54
1
Order By: Relevance
“…Further, those children below the 3rd percentile for weight at baseline reached normal growth after 2 years, but most of those below the 3rd percentile for height did not reach normal growth after 2 years. Previously published European studies found growth retardation of PKU patients during the first years of life was followed by restoration of normal growth [9,[22][23][24] A longitudinal study of Dutch children found that those with PKU had an almost identical height as other children of the same age [9]. Although normal growth appeared to be restored for weight in the current study, the normal growth for height for the PKU children was not restored.…”
Section: Discussioncontrasting
confidence: 54%
“…Further, those children below the 3rd percentile for weight at baseline reached normal growth after 2 years, but most of those below the 3rd percentile for height did not reach normal growth after 2 years. Previously published European studies found growth retardation of PKU patients during the first years of life was followed by restoration of normal growth [9,[22][23][24] A longitudinal study of Dutch children found that those with PKU had an almost identical height as other children of the same age [9]. Although normal growth appeared to be restored for weight in the current study, the normal growth for height for the PKU children was not restored.…”
Section: Discussioncontrasting
confidence: 54%
“…This recommendation, at that time very strict, can nowadays be found in general recommendations for treating PKU [15,25]. Details of the design and protocol as well of results have been reported elsewhere [3,5,19,[21][22][23]28] and in the present issue of the European Journal of Pediatrics. The data presented in this paper concentrate on the development of intelligence of the patients from 4 "to 9 years of life in relation to their blood Phe levels during the first 9 years of life.…”
Section: Introductionmentioning
confidence: 95%
“…The report by Dhondt et al [5] of growth of 94 French patients indicated that both at birth and at 8 years of age, mean Z-scores for height and weight were negative. Schaefer et al [21] reported that mean standard deviation scores (SDS) for height and weight at birth of 82 German Collaborative Study patients did not differ from 0. During the first 2 years of life, the mean SDS became negative but returned toward 0 during the following 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…Weglage et al [23] found negative mean Zscores for height during the first 18 months of life in 87 German patients. Only Schaefer et al [21] and Weglage et al [23] reported protein intakes and none reported energy intakes. Schaefer et al [21] reported that protein intake was 2.24 + 0.51 g/kg (mean + SD) during the first 2 years of life and 1.98 + 0.25 g/kg until 6 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation